Relationship between mandibular asymmetry and body posture: a literature review: Hubungan antara asimetri mandibula dan postur tubuh: sebuah kajian pustaka - Ardiansyah S. Pawinru; Nasyrah Hidayati; Ita Purnama Alwi (Makassar Dental Journal, 2022)
The aim of this study was to know issue of the relationship between mandibular asymmetry and body posture. The literatures of mandibular asymmetry and body posture published in the last 10 years (2012-2022) which were collected from the electronic databases PubMed and Google Scholar. The data obtained was anaylized using observational, prospective, retrospective, case reports, systematic reviews and meta-analyses, showed that there is a relationship between themandibular and C2-3 with the rela-tion of the suprahyoid, hyoid bone, infrahyoid and sternocleidomastoid muscles connecting to spine. So, the changes in mandi-bular position will also change the body posture, and body posture will also affect the position of the mandibular with spinal de-formities which results in distortion of the vertebral column and asymmetrical face, shoulders, and waist. It was concluded that all studies cited in this literature review reported thatmandibular asymmetry and body posture have a reciprocal relationship.